Effect of different sources of dietary fiber on growth, apparent digestibility of protein, fat and energy and protein utilization in rats - M. A. Osman; A. A. EL-Shamrany; M. S. Alamri; A. H. Al-Assaf; A. A. El-Othman; E. E. Babiker (Journal of Animal and Plant Sciences, 2014)
The study of the effects of dietary fibers on nutrients metabolism is complicated by the fact that the dietary fiber is not a homogeneous compound but consists of a variety of substances, including cellulose, hemicellulose, pectin, mucilage, gums, algal polysaccharides and lignin.  Therefore, in the present study we would like to determine the effect of gum Arabic (GA), carrgeenan (CR) compared to cellulose (CE) as a control on protein indices, fat and energy metabolism in rats.  Wistar strain male rats (36) weighing 45-50gm were randomly assigned to six experimental groups, six animals  to each group and housed individually in stainless steel metabolic cages.  Six diets, three of them contain GA, CR or CE (5.2%) and casein to give 10% protein.  Food intake, weight gain (WG), apparent digestibility of protein (APD), fat (AFD) and energy (AED), protein biological value (PBV), energy and amino acids apparent digestibility were determined. There was no significant (P≤0.05) difference in food intake between the groups.  There was a significant (P≤0.05) difference in WG between gum arabic group and other two groups. Addition of cellulose gave higher APD and that of gum arabic gave higher AFD and AED.  There was no significant (P≤0.05) difference in true protein digestibility between the groups but diets with CE or CR slightly gave high values. The biological value was higher for GA diet and no significant (P≤0.05) difference between the groups in net protein utilization. No significant (P≤0.05) difference in urine, fecal, intake and metabolic energy among the groups. The apparent amino acids digestibility varied significantly (P≤0.05) within and among the groups.  The results indicate that gum Arabic as a source of dietary fiber compared to carrgeenan and cellulose did not affect food intake and in the meantime improved nutrients metabolism in rats.
Keywords: gum arabic; carageenan; cellulose; apparent digestibility; energy; rats